Galileo Galilei, The Tuscan Artist - Greco, Pietro (Springer International Publishing, 2018)
This book is a distinctively original biography of Galileo Galilei, probably the last eclectic genius of the Italian Renaissance, who was not only one of the greatest scientists ever, but also a philosopher, a theologian, and a man of great literary, musical, and artistic talent - "The Tuscan Artist", as the poet John Milton referred to him. Galileo was exceptional in simultaneously excelling in the Arts, Science, Philosophy, and Theology. These diverse aspects of his life were closely intertwined; indeed, it may be said that he personally demonstrated that human culture is not divisible, but rather one, with a thousand shades. Galileo also represented the bridge between two historical epochs. As the philosopher Tommaso Campanella, a contemporary of Galileo, recognized at the time, Galileo was responsible for ushering in a new age, the Modern Age. This book, which is exceptional in the completeness of its coverage, explores all aspects of the life of Galileo, as a Tuscan artist and giant of the Renaissance, in a stimulating and reader-friendly way.